Utilization Of Mangrove Forest As Alternative Income For Coastal Communities In Sukakerta Village, Karawang (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The existence of mangrove forests are ecologically important because it supports the food chain in the area by protecting the coast from strong winds, abrasion/erosion, and tsunamis. Besides the ecological benefits, mangroves are also economically beneficial. The economic function is as a producer of wood for raw materials, building materials, and food. Besides that, the biota that lives in the mangrove ecosystem also has economic value if processed properly. This service activity was carried out in the Tengkolak hamlet, Sukakerta Village, Cilamaya Wetan District, Karawang Regency, which is not very familiar with the use of mangrove fruit and natural products so that it has high economic value and improves community welfare. Through KUB, the activity aims to improve the understanding and skills of the community on how to process mangrove fruit and biota in the ecosystem into various products as an alternative for additional income. The people who take part in this activity are people who are members of the KUB Kreasi Alam Bahari. The method of carrying out the activities is through demonstrations and training on making coffee from mangrove trees and the Talang-talang fish product variant, which has been developed into skin chips, nuggets, and fish balls. The evaluation process was carried out by interviewing several residents to ask for information and impressions of the activities that had been carried out. The community, especially those who participated in the activity, felt the positive impact of these activities. Because they can increase their skills in processing mangrove fruit and processing Talang-talang fish that have higher economic value.